Comparative education as cultural critique. Issue 1 (2nd January 2020) - Rappleye, Jeremy
ABSTRACT: Relating my experience of becoming a 'foreign' comparativist, I offer a vision of comparative education that both extends and challenges the field. It continues the work of Bereday and Lauwerys who sought to make visible the 'contrasting colours of the world' in order to affect deep self-reflection and imagine alternatives. But it also challenges that earlier iteration: calling for a drastic widening of the imaginative kosmos, an exorcising of our enduring Hegelian worldview, and more skilled work in bringing differences 'home'. It underscores the need for new modes of engagement: earnestness, humility, self-overcoming. Our time of heightened transnational academic mobility makes this sort of work practically possible for the first time, but the field's full potential to affect intellectual paradigms will occur only when we become immigrants of being.